ANALISIS METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Abdul Rachman Taufik; Dessy Rizki Suryani; Nurhayati Nurhayati (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2022)
This study was conducted to describe the metacognition of junior high school students in solving mathematical problems based on cognitive style. This type of research is a descriptive study using a qualitative approach which was carried out in class IX of SMP Negeri 2 Anggeraja. Results Based on the mathematical ability test and the Matching Familiar Figure Test (MFFT), 2 students were selected as research subjects. Data collection techniques were carried out by presenting problem-solving tasks and task-based interviews. Data analysis uses data reduction steps, data presentation, and drawing conclusions. The results of this study indicate that students with reflective cognitive style fulfill the three aspects of metacognition, namely planning, monitoring, and evaluating in solving problems. From the metacognitive activity of students with reflective cognitive style, it shows that the level of metacognitive ability is at the level of reflective use. Students with impulsive cognitive style fulfill the three aspects of metacognition, namely planning, monitoring, and evaluating in solving problems. However, at the planning stage only able to reveal some strategies that can be used to solve the problem and at the evaluation stage unable to prove the truth of the answers obtained. From the metacognitive activity of students with cognitive impulses, it shows that the level of metacognition ability is at the level of awareness of use